Thinking on the Meteorological Services to Ensure the Development of a System for New Energy Sources - Yongchang ZHU; Xiaofeng ZHANG; Zhenghong CHEN; Dong YE; Juan TAN; Yong QIN; Zhaohui LIU; Zhiqi XU (南方能源建设)
[Objective] Clean and low-carbon production is the core target of a system for new energy sources, and which construction is an important measure to realize the carbon peaking and carbon neutrality goals. Meteorological factors and disasters have great impacts on the stable and safe operation of the power grid. It is necessary to build a high-quality meteorological service system according to the needs of the construction of a system for new energy sources. [Method] In this paper, literature and policy research and expert consultation methods were adopted. Based on the analysis of the relevant policie measures of a system for new energy sources, the future development direction of the energy meteorological service was studied, and the development proposals of the meteorological service system for the construction of a system for new energy sources were put forward. [Result] The research shows that service departments at various levels of China Meteorological Administration have deliverd energy meteorological services in wind power, solar power, hydropower, nuclear power, power grid operation, energy consumption etc. The construction of a system for new energy sources puts forward new requirements for meteorological service, such as optimizing the overall layout of meteorological service support for the construction of clean energy bases, strengthening the accuracy of power generation forecast and climate prediction services, and carrying out meteorological service support for various scenarios such as the construction of new energy infrastructure, power generation, storage, transmission and consumption. [Conclusion] According to the requirements of a system for new energy sources construction, proposals are put forward from aspects such as optimizing the layout of meteorological services, improving service support capabilities, strengthening talent and cooperation mechanisms.